2021
DOI: 10.3389/fphys.2021.707634
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mitofusin-2 Enhances Mitochondrial Contact With the Endoplasmic Reticulum and Promotes Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy has been associated with mitochondrial damage. Mitochondria–endoplasmic reticulum (ER) contact is an important determinant of mitochondrial function and ER homeostasis. We therefore investigated whether hyperglycemia can damage the mitochondria by increasing their contact with the ER in cardiomyocytes. We found that hyperglycemia induced mitochondria–ER contact in cardiomyocytes, as evidenced by the increased MMM1, MDM34, and BAP31 expressions. Interestingly, the silencing of Mfn2 reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Similarly, hyperglycaemia increases mitochondria–ER contact and Ca 2+ levels in the ER and mitochondria of cardiomyocytes. However, Mfn2 silencing reduces mitochondria-ER cooperation, Ca 2+ concentrations in both ER and mitochondria, mitochondrial ROS production, ER stress and mitochondria-mediated apoptosis, preserving mitochondrial function and cardiomyocyte viability under hyperglycaemic conditions [ 45 ].…”
Section: Mitochondrial Dynamics In Dcmmentioning
confidence: 99%
“…Similarly, hyperglycaemia increases mitochondria–ER contact and Ca 2+ levels in the ER and mitochondria of cardiomyocytes. However, Mfn2 silencing reduces mitochondria-ER cooperation, Ca 2+ concentrations in both ER and mitochondria, mitochondrial ROS production, ER stress and mitochondria-mediated apoptosis, preserving mitochondrial function and cardiomyocyte viability under hyperglycaemic conditions [ 45 ].…”
Section: Mitochondrial Dynamics In Dcmmentioning
confidence: 99%
“…DC is currently considered to be a cause of high mortality in patients with diabetes, and there is no effective treatment [65]. More and more studies indicate that ER stress is involved in DC [66][67][68]. Larry A. Barr and colleagues fed rats with a high-fat diet (HFD) to establish a diabetes rat model and then performed a series of experiments.…”
Section: Hydrogen Sulfide Improves Diabetic Cardiomyopathy By Regulat...mentioning
confidence: 99%
“…In recent years, studies have found that ER stress and mitochondrial apoptosis pathways may be involved in the progression of DCM, and myocardial cells in DCM patients are accompanied by glucose and lipid metabolism disorders, producing large amounts of reactive oxygen species (ROS). This leads to ER swelling and mitochondrial structure and function disorders, which in turn cause myocardial hypertrophy, interstitial fibrosis, myocardial necrosis, and apoptosis ( Zhou et al, 2018b ; Ljubkovic et al, 2019 ; Zhang J. et al, 2021 ).…”
Section: The Critical Role Of Endoplasmic Reticulum-mitochondria Contacts In Remodeling and Cardiovascular Remodeling-associated Diseasesmentioning
confidence: 99%
“…In addition, MAMs’ constitutive proteins may be involved in the pathogenesis of diabetic cardiomyopathy, for example, Mfn2 and FUNDC1. These protein bridges of MAMs could be potential therapeutic targets for DCM in the future ( Wu et al, 2019 ; Zhang J. et al, 2021 ). A recent work showed that Mfn2 promotes ERMCs in cardiomyocytes subjected to hyperglycemic conditions.…”
Section: The Critical Role Of Endoplasmic Reticulum-mitochondria Contacts In Remodeling and Cardiovascular Remodeling-associated Diseasesmentioning
confidence: 99%
See 1 more Smart Citation